Screening Performance of Stroke Scale for Mid-Level Personnel (SML) in Detecting Acute Stroke with Large Vessel Occlusion: A Cross-sectional Study - Rojanasarntikul, Dhanadol; Chutinet, Aurauma; Lerthirunvibul, Nichapa; Pechudom, Sivapan (Archives of Academic Emergency Medicine, 2025)
Introduction: The stroke scale for the mid-level personnel (SML) was designed for emergency medical services personnel to predict acute ischemic stroke due to large vessel occlusion (LVO) in both prehospital and in-hospital settings. This study aimed to validate and determine the appropriate cut point of the SML score in this regard. Methods: This single-centered, prospective validation study to assess a novel LVO triage tool was performed in a tertiary care hospital in Bangkok. Patients presenting within 24 hours of onset of acute stroke were included in the study. The scale is designed for mid-level providers and emergency medical services (EMS) personnel including paramedics, emergency medical technicians (EMTs) and emergency department (ED) nurses. LVO was confirmed by brain and neck computed tomography angiography (CTA). Area under the receiver operating characteristic (ROC) curve, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), likelihood ratios (LRs), and correctly classified instances (CCI) were calculated. Youden’s index was used to determine an appropriate cut point of the SML score for LVO prediction. Results: 200 cases with the median age of 64.0 (56.5-73.0) years were included (53.5% female). 83 (41.5%) cases were affiliated to the LVO and 117 (58.5%) to the non-LVO group. The median SML scores for non-LVO and LVO stroke patients were 3 (2 - 3) and 6 (5 - 7), respectively (p < 0.001). The most common presentations in both groups were facial palsy, arm weakness and speech impairment or dysarthria. There was significantly higher prevalence of neglect (8 (6.8%) vs. 5 (4.3%); p < 0.001) and eye deviation (39 (47%) vs. 29 (35%); p < 0.001) in the LVO stroke group than in the non-LVO group. LVO patients scored higher in all categories when compared to non-LVO cases. SML scores of 4 and 5 had the highest Youden's index of 0.82 and 0.67, respectively. SML score of 4 yielded the highest correctly classified instances (CCI) of 90% with sensitivity and specificity of 96.4% (95% confidence interval (CI): 89.9-99.3%) and 85.3% (95% CI: 77.6-91.2), respectively. SML score of 4 also achieved the lowest negative LR of 0.04 and an odds ratio of 157 (95% CI: 46.7-521). The AUC of SML in cutoff point of 4 was 0.901 (95%CI: 0.853 - 0.949). Conclusions: SML score may be helpful for mid-level medical providers and also EMS personnel in detecting LVOs since prehospital phase. According to the results, we recommend a cut point SML score ≥ 4 for enhanced sensitivity and NPV.